Capitan Chiquito : a personal history of an Apache Chief, 1821-1919 - Hartman, John Paul, 1951- (Elma Dill Russell Spencer series in the West and Southwest, 2022)
"Drawn from personal recollections, historical records, and biographical research, Capitan Chiquito: A Personal History of an Apache Chief, 1821-1919 relates the little-known life and career of a leader of the Aravaipa band of Apaches during the late nineteenth and early twentieth centuries. During his nearly 100 years of life, Chief Capitan Chiquito spent time in prison with Geronimo; defended his home territory in Aravaipa Canyon from the depredations of Anglo-Americans, Mexicans, and rival Native American tribes; suffered the brutal massacre and abduction of many of his people; and ultimately won from the federal government the right to live on and cultivate his canyon homestead. He died in 1919 at the age of 98 from complications of influenza while caring for ill members of his clan. In the opening pages, author John Paul Hartman reminisces about some of the people he has loved-and lost-during his time on the San Carlos Reservation in southeastern Arizona. His wife, Velma Bullis, great-granddaughter of Chief Capitan Chiquito; her father, Lonnie, the chief's grandson; and many others have preceded him through "the Western portal," departing this life. "There is nothing for me here in San Carlos now," he writes. "It is time for me to leave . . . But before they will let me go, I have a story to tell." As Hartman ends this work, he explains that he undertook the research and writing about his wife's ancestor as a means of closure for his two decades of life on the San Carlos Reservation. With the care of a historian and the dedication of an enthusiast, he has followed the trail of this notable leader, affording readers a unique view of a previously little-known yet intensely revealing historical narrative"--